Perlindungan Hukum terhadap Identitas Batik Merawit Cirebon Sebagai Produk Indikasi Geografis: Tinjauan Realistis dalam Hukum Kekayaan Intelektual di Indonesia - Utami, Devi Citra; Wijayanti, Fahira Salsabila; Ginanjar, Yaumi Sidik (Wajah Hukum, 2025)
The purpose of this study is to analyze the legal protection of Cirebon Merawit Hand-drawn Batik as a geographical indication product, the challenges and implications of geographical indication protection for craftsmen and the local economy. The method used in this study with a 4-month activity design with a scope related to intellectual property rights in geographical indications, the main materials and tools used are primary data sources, secondary data sources and tertiary data sources. Data collection techniques in the form of interviews and documentation so that the analysis technique is descriptive analytical. The results of this study are an analysis of the legal protection of Cirebon Merawit Hand-drawn Batik as a geographical indication product is to prevent counterfeiting and unauthorized use, increase competitiveness and economic value and maintain the sustainability of local culture and heritage. Then the challenges in the Implementation of Geographical Indication Protection are the lack of awareness and socialization, violations and counterfeiting that still occur and global competition and the implications of Geographical Indication Protection for Craftsmen and the Local Economy are increasing craftsmen's income, local economic development and protection of local community rights.